Harnessing ChatGPT for Effective Assessment and Feedback in Education - Sain, Zohaib Hassan; Vasudevan, Asokan; Thelma, Chanda Chansa; Asfahani, Asfahani (Journal of Computer Science and Informatics Engineering, 2024)
Incorporating artificial intelligence (AI) into educational settings has been thrust forward using information and communication technology to improve the teaching and learning processes. In November of 2022, a significant advancement in this field occurred with the launch of ChatGPT, a chatbot powered by artificial intelligence. This cutting-edge chatbot can create logical and instructive replies, much like those that human users generate. Because of its versatility, ChatGPT has emerged as a potential supporter of open education. It offers helpful assistance, coaching, and feedback to learners who are self-directed, which in turn increases the learners' levels of motivation and engagement. This article aims to conduct an in-depth comparison and analysis of the elements above, focusing on the possible uses of ChatGPT inside educational settings. The particular goals include lobbying for adopting ChatGPT in academic settings and providing educators with various strategies and approaches to use ChatGPT in a manner that is both deliberate and successful in pedagogical or research endeavours. One of the primary objectives of this study is to encourage a well-informed discussion on the use of ChatGPT in educational settings. When it comes to incorporating ChatGPT services into educational environments, it outlines the fundamental techniques and approaches that should be used simultaneously.